2017
DOI: 10.1136/inp.j1083
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ovariectomy in small animals

Abstract: Ovariectomy and ovariohysterectomy are the two most commonly used techniques for sterilisation of female small animals. In the past decade, there has been a trend towards using minimally invasive techniques in small animal surgery, and laparoscopic ovariectomy (LapOVE) has emerged as one of the most common clinical applications of laparoscopy in small animals. LapOVE offers several advantages over the open method conducted through the median coeliotomy, including reduced postoperative pain, faster recovery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In their study, the intra-peritoneal CO 2 pressure was 5 mmHg. However, a higher intra-peritoneal CO 2 pressure allows for the good visualisation of the reproductive organs (this study; Rutherford and Finding 2009;Katic and Dupre 2017;Daniel et al 2019).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In their study, the intra-peritoneal CO 2 pressure was 5 mmHg. However, a higher intra-peritoneal CO 2 pressure allows for the good visualisation of the reproductive organs (this study; Rutherford and Finding 2009;Katic and Dupre 2017;Daniel et al 2019).…”
Section: Discussionmentioning
confidence: 94%
“…However, Case et al (2011) reported that there were no significant differences in the surgical time between the two and three port techniques, while the single port technique took a significantly longer time in bitches. Moreover, the surgical time is also highly dependent on the type of vessel-sealing devices used (Katic and Dupre 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical ventilators are present in 30.1% of the practices, which is relatively high compared to 14.1% of the practices in New Zealand (Sano et al, 2018), 25.0% in Quebec (Truchetti et al, 2020) and comparable to 28.0% of the practices in France (Farges, 2012). With an increased interest in laparoscopic procedures for gonadectomies (Katić and Dupré, 2017;Marvel, 2022), the presence of mechanical ventilators in practices is suspected to increase in the coming years, since they are a prerequisite to safely perform laparoscopic procedures (de Rezende and Mama, 2022).…”
Section: Discussionmentioning
confidence: 99%